2022
DOI: 10.1111/are.16058
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sources improve water quality, microbial community, immune‐related and antioxidant genes expression and survival of challenged Litopenaeus vannamei Postlarvae in biofloc system

Abstract: The influence of different processed agriculture wastes as carbon sources including sugarcane bagasse (SCB), rice bran (RB) and rice straw (RS) on water quality, microbial community, and expression of immune‐related and antioxidant genes in both hepatic and muscle tissues was evaluated. Furthermore, the cumulative mortality rates of Litopenaeus vannamei when challenged with Vibrio and Shewanella algae were estimated. The experiment lasted for 3 months in outdoor culture ponds, and the results indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Based on the findings of the current study, it appears that seaweed polysaccharide extraction may increase the expression of growth-related genes at the mRNA level, hence boosting growth capacity indirectly. Other studies examining the impact of employing different carbon sources for boosting IGF-I and IGF-II gene expression revealed similar outcomes [ 123 ]. Furthermore, utilizing the green microalga, T. suecica, and A. platensis nanoparticles as the supplementary feeds for L. vannamei greatly increased the expression of both genes and improved growth [ 22 , 100 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Based on the findings of the current study, it appears that seaweed polysaccharide extraction may increase the expression of growth-related genes at the mRNA level, hence boosting growth capacity indirectly. Other studies examining the impact of employing different carbon sources for boosting IGF-I and IGF-II gene expression revealed similar outcomes [ 123 ]. Furthermore, utilizing the green microalga, T. suecica, and A. platensis nanoparticles as the supplementary feeds for L. vannamei greatly increased the expression of both genes and improved growth [ 22 , 100 ].…”
Section: Discussionmentioning
confidence: 76%
“…Thus, both stress genes in this study are significantly upregulated in comparison to the control group, and the activities of the SOD and GPx increase together with an increase in superoxide anion (O 2 − ) and hydrogen peroxide (H 2 O 2 ), which may indicate increases in the activity of NADPH-oxidase and the production of a mass of reactive oxygen species (ROS) that can represent as a defense mechanism against microbial infection [ 73 , 122 ]. Recent research has evaluated the expression of genes involved in immunity in shrimp [ 123 , 124 ] and has concentrated on ways to boost their natural defenses.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Hassan et al. (2022) also demonstrate the ability of biofloc to enhance the gene expression of LGBP and PO in systems with different carbon sources compared to the control treatment. Furthermore, Kim et al.…”
Section: Discussionmentioning
confidence: 88%
“…This melanin-related activity is referred to as melanization (Amparyup et al, 2013). The results of Hassan et al (2022) also demonstrate the ability of biofloc to enhance the gene expression of LGBP and PO in systems with different carbon sources compared to the control treatment. Furthermore, Kim et al (2014), reported an increase in the expression of the SP gene in white shrimp postlarvae reared in biofloc systems.…”
Section: Discussionmentioning
confidence: 90%
“…Biofloc technology (BFT) has been widely applied worldwide to reduce environmental impact and the production cost through well manage heterogenous mixture of heterotrophic bacteria, macroalgae, food, faecal, remnants, exoskeletons, invertebrates into grown flocs and its ability to maintain good water quality [6,7] and disease resistance as a whole can increase the production of various aquaculture species such as shrimp (Litopenaeus vannamei) and fish (Tilapia nilotica) [8,9]. Organic wastes from bioflocs of shrimp (L. vannamei) farming that are truncated to the surrounding waters after the harvesting periods may slightly affect the survival and physiological conditions of various gastropod species [10] as well as abalone cultivated in the coastal waters surrounding shrimp farming area by increasing turbidity that can affect water work.…”
Section: Introductionmentioning
confidence: 99%